1984
DOI: 10.1083/jcb.98.2.685
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of synaptic vesicle membrane at the frog neuromuscular junction.

Abstract: Frog nerve-muscle preparations were quick-frozen at various times after a single electrical stimulus in the presence of 4-aminopyridine (4-AP), after which motor nerve terminals were visualized by freeze-fracture . Previous studies have shown that such stimulation causes prompt discharge of 3,000-6,000 synaptic vesicles from each nerve terminal and, as a result, adds a large amount of synaptic vesicle membrane to its plasmalemma . In the current experiments, we sought to visualize the endocytic retrieval of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
258
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(286 citation statements)
references
References 29 publications
27
258
1
Order By: Relevance
“…With respect to DYNAMIN, which is known to complete vesicle formation through membrane fission (44), previous studies have shown it is also present and functionally important at early stages of CLATHRIN-mediated endocytosis (45,46). AZ localization of endocytic proteins might suggest a mechanism of release site clearance involving rapid formation of CLATHRIN-coated vesicles directly from the AZ; however, this mechanism is not favored, primarily because ultrastructural studies indicate that CLATHRIN-coated vesicles form at PAZ, rather than AZ, regions of the plasma membrane (47,48) (Fig. 4B, iii).…”
Section: Rapid Endocytic Mechanisms Maintaining Neurotransmitter Releasementioning
confidence: 91%
See 1 more Smart Citation
“…With respect to DYNAMIN, which is known to complete vesicle formation through membrane fission (44), previous studies have shown it is also present and functionally important at early stages of CLATHRIN-mediated endocytosis (45,46). AZ localization of endocytic proteins might suggest a mechanism of release site clearance involving rapid formation of CLATHRIN-coated vesicles directly from the AZ; however, this mechanism is not favored, primarily because ultrastructural studies indicate that CLATHRIN-coated vesicles form at PAZ, rather than AZ, regions of the plasma membrane (47,48) (Fig. 4B, iii).…”
Section: Rapid Endocytic Mechanisms Maintaining Neurotransmitter Releasementioning
confidence: 91%
“…4). Particle clusters were thought to dissipate after vesicle fusion (51), and further analysis suggested they may reassemble within CLATHRIN-coated pits at the PAZ (47). In contrast, recent superresolution light microscopy studies showed that native synaptic vesicle proteins deposited in the plasma membrane from different vesicles do not mix before endocytosis but, instead, remain in distinct clusters and are retrieved separately (53).…”
Section: Rapid Endocytic Mechanisms Maintaining Neurotransmitter Releasementioning
confidence: 99%
“…There are four major modes of endocytosis to differentiate, referred to as: kiss-and-run of synaptic vesicles, estimated to occur in <1 s time-frame [51]; clathrin-mediated endocytosis (CME), occurring in a 10-20 s time-frame [52][53][54][55]; ultrafast endocytosis followed by endosomal budding (initial membrane retrieval 100 ms, vesicle recovery 5-6 s) [56]; and bulk endocytosis [57]. Mechanisms of clathrin-mediated endocytosis are well established and many key players are known today; however, mechanisms for the kiss-and-run mode are under sustained debate and a molecular identity involved in the process is still missing.…”
Section: Mechanisms Of Synaptic Vesicle Endocytosismentioning
confidence: 99%
“…The recycling is accomplished in less than 1 min by a series of steps beginning with a very efficient endocytic retrieval of synaptic vesicle components and culminating with the regeneration of releasable synaptic vesicles (Heuser and Reese, 1973;Miller and Heuser, 1984;Valtorta et al, 1988;Ryan and Smith, 1995; for reviews see Betz and Wu, 1995;De Camilli and Takei, 1996).…”
mentioning
confidence: 99%